Senyawa Metabolit Sekunder dan Aspek Farmakologi dari Alocasia macrorrhizos - Yuliana Yuliana; Sri Fatmawati (LPPM, Institut Teknologi Sepuluh Nopember, 2018)
Alocasia macrorrhizos or sente hijau is a traditional medicinal plant in Celebes - Indonesia. The secondary metabolite compounds have been isolated from the root, rhizome and leaves of the plant. From the root part, aloceramide compounds have been isolated, whereas rhizome containing lignanamide, monoindole, indole and piperidin compounds and leaves have triglochinin and isotriglochinin components. Furthermore, the plant also has biological activities such as antidiuretic, anticancer, antioxidant, antimicrobial, antidiabetic, antihyperglycemia and others. This review aims to report the secondary metabolite compounds and the biological activity of A. macrorrhizos to provide scientific evidences for the plant as a folk medicines.